Joint power allocation and beamforming for active IRS-aided secure directional modulation network - Dong, Rongen; Shu, Feng; Li, Yongzhao; Tang, Yanqun; Li, Jun; Wu, Yongpeng; Wang, Jiangzhou (Science China. Information sciences, 2025)
To boost the secrecy rate (SR) of the conventional directional modulation (DM) network and overcome the “double fading” effect of the cascade channels of the passive intelligent reflecting surface (IRS), a novel active IRS-aided DM system with a power adjustment strategy between transmitter and active IRS is proposed in this study. Then, the SR is maximized by jointly optimizing the power allocation (PA) factors, transmit beamforming, receive beamforming, and reflect beamforming at the active IRS, subject to the IRS power constraint. To solve the formulated non-convex optimization problem, a high-performance scheme of maximizing SR based on successive convex approximation (SCA) and Schur complement, called Max-SR-SS, is proposed, where the derivative operation is employed to optimize the PA factors, the generalized Rayleigh-Ritz theorem is adopted to derive the receive beamforming, and the SCA strategy is utilized to design the transmit beamforming and IRS phase shift matrix. To reduce the high complexity, a low-complexity scheme of maximizing SR based on equal amplitude reflecting (EAR) and majorization-minimization (MM), called Max-SR-EM, is developed, where the EAR and MM methods are adopted to derive the amplitude and phase of the IRS phase shift matrix, respectively. In particular, when the receivers are equipped with single antenna, a scheme of maximizing SR based on alternating optimization, called Max-SR-AO, is proposed, where the PA factors, transmit beamforming, and reflect beamforming are derived by the fractional programming and SCA algorithms. The simulation results show that, with the same power constraint, the SR gains achieved by the proposed schemes outperform those of the fixed PA and passive IRS schemes.